HOW TO IMPROVE SPEAKING SKILL FOR YOUNG LEARNERS - Normurodova, Gulshoda Shukurilla qizi; Sayidova, Sarvinoz Nurtosh qizi; Burkhanova , Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
This article provides a brief overview of how to develop young students’ speaking skills, what grammar rules to use, and how to improve their English speaking skills.